Inżynieria pojęciowa a teorie zarządzania i organizacji - Piotr Tomasz Makowski (Studia i Materiały)
The text is an attempt at showing the need of conceptual engineering (and its competences) on the terrain of Organization and Management Theory (OMT). The author defends the view that consistent use of conceptual engineering on the area of OMT allows to improve its conceptual-theoretical standards. This may positively affect its scientific and practical qualities. A critical analysis of selected examples of conceptualization in theory of organizational routines (important part of OMT) brings the following conclusion: the role of the use of conceptual engineering in OMT for its theoretical standards is similar to the role of compliance to methodology of inquiry for the overall empirical dimension of management sciences.